1993
DOI: 10.1017/s0317167100047685
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Features of Vestibular Schwannoma in Manitoba, Canada

Abstract: ABSTRACT:The incidence of vestibular schwannoma (acoustic neuroma) in Manitoba, Canada was reviewed. From 1987 through 1991, 71 tumors were diagnosed in 69 patients. The overall annual incidence rate for both sexes was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
(10 reference statements)
1
12
0
Order By: Relevance
“…The incidence in Denmark is also higher than Finland, Norway, and Sweden [14]. An incidence similar to the US was found in a Canadian study [12]. International differences in vestibular schwannoma incidence may be due to different genetic and/or environmental factors or due to differences in diagnostic practices.…”
Section: Study Interpretationsupporting
confidence: 50%
See 1 more Smart Citation
“…The incidence in Denmark is also higher than Finland, Norway, and Sweden [14]. An incidence similar to the US was found in a Canadian study [12]. International differences in vestibular schwannoma incidence may be due to different genetic and/or environmental factors or due to differences in diagnostic practices.…”
Section: Study Interpretationsupporting
confidence: 50%
“…We believe this represents the most accurate and complete estimate of the incidence of vestibular schwannoma in the US to date. The incidence of vestibular schwannomas varies internationally [11][12][13][14][15][16][17][18][19][20]. International rates are age-adjusted to the world standard million and cannot be directly compared to rates adjusted to the US standard million.…”
Section: Study Interpretationmentioning
confidence: 99%
“…One autopsy study 2 suggests that acoustic neuromas may be present in 2.4% of individuals dying from unrelated causes. This histologic incidence greatly exceeds the incidence of symptomatic tumors, which has been estimated as about 1 new case per 100,000 population per year 3‐5 …”
Section: Introductionmentioning
confidence: 95%
“…Several other studies have also published data showing an increasing incidence rate of VS. Generally, incidences between 10 and 20 VS/million/year are reported, including data from America (Nestor et al8), Canada (Frohlich and Sutherland9), United Kingdom (Evans et al10) and locally in Denmark (Mirz et al11). Lately, American population-based registry studies have found similar incidences.…”
Section: Introductionmentioning
confidence: 99%